Zakho in the Newspaper of Mosul 1921-1930 - Tawfiq, Hoger T.; Sheikho, Wasfia Mohamed (Humanities Journal of University of Zakho, 2017)
Any researcher in the field of history cannot diminish the role of the journalist because they are known for preserving information about historical situations. If the task of the press is important for other nations, then it is more important for the Kurds. The Kurds lost their historical files until after World War II as a result of the political situation that they went through. The Kurdish authors did not write about their history, resulting in only a few compositions, therefor, press had an important role in saving Kurdish historical information in many areas both regional Kurdish press and foreign.One of those journalisms was the Mosul Newspaper which was issued in the city of Mosul, in the Arabic language. During that time Zakho was under Mosul’s administration. Therefor we find that the Mosul Newspaper contains critical information about Zakho in general, particularly its city centre. The information published by this newspaper is not seen in other historical resources for that time. For this reason, this newspaper is a significant source for Zakho town. It covers the developments during the period 1921-1930 in various areas of life.